Efficacy of Extractions of Iranian Native Plants against Main Malaria Vector, Anopheles stephensi in Iran for Making Appropriate Formulation for Disease Control - Hassan Vatandoost; Fatemeh Nikpour; Ahmad Ali Hanafi-Bojd; Mohammad Reza Abai; Mahnaz Khanavi; Abbas Hajiiakhondi; Ahmad Raesi; Jalil Nejati (Tehran University of Medical Sciences, 2019)
Background: Malaria is the main vector-borne disease worldwide. There are several reports of insecticide resistant in malaria vectors worldwide due to using different insecticides. The aim of this study was to evaluate different native plant extortions against main malaria vector, Anopheles stephensi in Iran for choosing the appropriate plant for formulation and use for vector control. Methods: The larvae of An. stephensi were reared in insectary, extraction of plants were carried out at department of Pharmacology. The standard WHO method for biological tests was used for calculation of LC50 and LC90. Probit regration lines were plotted for calculation of LC50 and LC90. Results: In this study several plants including: Mentha spicata, Cymbopogon olivieri, Azadirachta indica, Melia azedarach, Lagetes minuta, Calotropis procera, Eucalyptus camaldulensis, Cupressus arizonica, Thymus vulgaris, Lawsonia inermis, Cedrus deodara, Cionura erecta, Bunium persicum, Carum carvi, Artemisia dracunculus, Rosmarinus officinalis were used. Results showed that Mentha spicata and Eucalyptus camaldulensis, had the lowest and highest LC50 respectively. Conclusion: Results indicated that Mentha spicata and Eucalyptus camaldulensis, had the lowest and highest LC50 respectively. Several other plant extract also showed significant mortality. The formulation of these plants should be prepared and evaluate at the field condition against malaria vectors.